Urbanização do Rio de Janeiro no início do século XX: entre o real e o oficial na crônica de Lima Barreto - INÁCIO, Cidney de Oliveira (2013)
The aim of this study is to study the transformations that the country's Federal Capital, the city of Rio de Janeiro, was suffering the early twentieth century due to urban intervention planned by the political authorities of the time, specifically in the office of Mayor Pereira Passos, whose Europeanizing purpose was to provide air to the city, namely to promote a drastic change in its urban layout. Parallel interference aesthetic highlights the chronic Lima Barreto, writer-witness this historic moment, which records the absence of projects that meet the needs of the poor, were slum dwellers who were born at this time as well as the tenements and houses of room contrasted with the landscape constituted, is in large parts of the homeless and unwanted by the public who took refuge in the suburbs, passing this way to give this author a prominent place in his writings to these spaces as well for this marginalized section of population . In this sense the focus of analysis is the interdisciplinary reading of this literary-historical process to better elucidate the intervention promoted by the Republic in the architectural layout of the Federal Capital, as well as all the symbolism that such action had.